(untitled) (Biological Sciences - PJSIR, 2015)
The study was planned to assess the nitrogen status of apple orchards around Quetta valley, Pakistan, through soil and plant analysis. Two hundred and forty soil samples were collected from 40 different locations of 05 orchards at 0-15, 15-30, 30-45, 45-60, 60- 75 and 75-90 cm depths. The soil samples were analysed for total nitrogen by Kjeldhal?s method. At the same time forty apple trees were selected for leaves samples and analysed for the total nitrogen content. Total nitrogen content in soil showed a sizeable variation ranging from 0.009 to 0.148%. Whereby, plant analysis registered minimum nitrogen content 1.06% and the maximum nitrogen content were 3.14% in apple plant leaves which confirms a great deficiency of nitrogen in apple orchards of Quetta valley.